2022
DOI: 10.2337/db22-0568
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Endogenously Secreted GLP-1 and GIP for Postprandial Glucose Tolerance and β-Cell Function After Roux-en-Y Gastric Bypass and Sleeve Gastrectomy Surgery

Abstract: Enhanced secretion of glucagon-like peptide-1 (GLP-1) seems to be essential for improved postprandial β-cell function after Roux-en-Y gastric bypass (RYGB) but is less studied after sleeve gastrectomy (SG). Moreover, the role of the other major incretin hormone, glucose-dependent insulinotropic polypeptide (GIP), is relatively unexplored after bariatric surgery. We studied the effects of separate and combined GLP-1 receptor (GLP-1R) and GIP receptor (GIPR) blockade during mixed meal tests in unoperated (CON), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…The most robust glycemic and β-cell effects of endogenous GLP-1 in our experiment, particularly in GB subjects, were observed during post-OGTT nadir glycemic levels where the plasma concentrations of GLP-1 return to baseline. This is consistent with a recent study which reported a significant increase in nadir glucose concentrations, as well as AUC glucose after the first hour of meal study, after GLP-1R blockade in GB and SG(19).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The most robust glycemic and β-cell effects of endogenous GLP-1 in our experiment, particularly in GB subjects, were observed during post-OGTT nadir glycemic levels where the plasma concentrations of GLP-1 return to baseline. This is consistent with a recent study which reported a significant increase in nadir glucose concentrations, as well as AUC glucose after the first hour of meal study, after GLP-1R blockade in GB and SG(19).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we did not measure active GIP, however, it can be assumed that a GIP is also increased in parallel to a GLP-1. However, it is unlikely that increased disposition index as observed in in GB subjects in the present study is mediated by enhanced a GIP since blocking GIPR in patients with GB has no effect on post-meal ISR or glucose concentrations(19). Furthermore, our findings can’t give insights into glycemic effects of DPP4i in bariatric subjects with diabetes since our subjects had no known history of diabetes.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The weight-loss independent glycemic effect of gastric bypass surgery (GB) and sleeve gastrectomy (SG) has been partly attributed to altered prandial nutrient flux and metabolism mediated by enhanced secretion of insulinotropic gut factors, mainly glucagon-like peptide 1 (GLP-1) [1][2][3][4]. GLP-1 is a product of the preproglucagon gene, mainly secreted by intestinal Lcells in proportion to amount of ingested nutrient and acts through GLP-1 receptor (GLP-1R) expressed in various tissues including islet cells and specific brain regions [5].…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that GLP-1R blockade has a greater effect to reduce the prandial insulin secretory response after gastric bypass (GB)[2, 4, 911] or sleeve gastrectomy (SG)[1], where both prandial GLP-1 secretion and glycemic excursion are augmented. Further, the increased insulinotropic effect of GLP-1 after GB is exaggerated in a discrete population suffering from the syndrome of hyperinsulinemic hypoglycemia and blocking GLP-1 action can correct hypoglycemia in affected patients, indicating that enhanced GLP-1-stimualted insulin secretion is a pathogenic factor in post-GB hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%